Whole Blood Mycobacterial Growth Assays for Assessing Human Tuberculosis Susceptibility: A Systematic Review and Meta-Analysis - Bok, Jeroen; Hofland, Regina W.; Evans, Carlton A. (Frontiers in Immunology, 2021)
Background. Whole blood mycobacterial growth assays (WBMGA) quantify mycobacterial growth in fresh blood samples and may have potential for assessing tuberculosis vaccines and identifying individuals at risk of tuberculosis. We evaluated the evidence for the underlying assumption that in vitro WBMGA results can predict in vivo tuberculosis susceptibility. Methods. A systematic search was done for studies assessing associations between WBMGA results and tuberculosis susceptibility. Meta-analyses were performed for eligible studies by calculating population-weighted averages. Results. No studies directly assessed whether WBMGA results predicted tuberculosis susceptibility. 15 studies assessed associations between WBMGA results and proven correlates of tuberculosis susceptibility, which we divided in two categories. Firstly, WBMGA associations with factors known to reduce tuberculosis susceptibility was statistically significant in all 8 studies of: BCG vaccination; vitamin D supplementation; altitude; and HIV-negativity/therapy. Secondly, WBMGA associations with probable correlates of tuberculosis susceptibility was statistically significant in 3 studies of tuberculosis disease, in a parasitism study and in 2 of the 5 studies of latent tuberculosis infection. Meta-analyses for associations between WBMGA results and BCG vaccination, tuberculosis infection, tuberculosis disease and HIV infection revealed consistent effects. There was considerable methodological heterogeneity. Conclusions. The study results generally showed significant associations between WBMGA results and correlates of tuberculosis susceptibility. However, no study directly assessed whether WBMGA results predicted actual susceptibility to tuberculosis infection or disease. We recommend optimization and standardization of WBMGA methodology and prospective studies to determine whether WBMGA predict susceptibility to tuberculosis disease.